ALMOST PERIODICITY IN SPECTRAL ANALYSIS REPRESENTATIONS INDUCED BY GENERALIZED SHIFT OPERATION - Karakhanian, M.I. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2012)
The famous Theorem of Yu. Lubich allows us in the language of the almost periodicity to get the criterion of completeness of the eigenvectors of a Hermitian compact operator in a weakly complete Banach space. In this paper this result is strengthened for the representation generated by the operation of the generalized shift.